Elastohydrodynamic lubricated cylindrical joints for rigid-flexible multibody dynamics - Tian, Qiang (2013)
A new methodology for dynamic analysis of rigid-flexible multibody systems with elastohydrodynamic (EHD) lubricated cylindrical joints is proposed. The EHD lubricated cylindrical joint is formulated by the Natural Coordinate Formulation (NCF) and the twenty- node hexahedral element of Absolute Nodal Coordinate Formulation (ANCF), being the lubricant pressure determined through the resolution of the Reynolds’ equation employing the finite difference method. The main outcomes are validated with those obtained by using the commercial software ADINA. It is shown that the bearing flexibility plays a significant role in the system responses, extends the lubricant distribution space and, consequently, reduces the lubricant pressure.